Status Hukum dan Perlindungan Jaminan Sosial terhadap Pekerja Ojek Online dalam Perspektif Hukum Ketenagakerjaan Indonesia - Muhammad Raqel Elang Pangestu; Henry Arianto (DOKTRINA: JOURNAL OF LAW, 2026)
The development of digital transportation technology has led to the rise of online motorcycle taxis as an application-based economic innovation that employs a large workforce. However, classifying drivers as partners rather than workers has created legal issues, particularly regarding labor protection and social security. This study analyzes the legal status of online motorcycle taxi drivers under Indonesian labor law and examines the form of social security protection available in Indonesia and several other countries. Using a normative-empirical legal method with a qualitative approach, data were obtained through statutory review, literature study, and interviews with drivers, platform operators, and the Department of Manpower. The results show that the relationship between platforms and drivers meets the elements of work, wages, and control that legally define an employment relationship, despite being formally categorized as a partnership. Consequently, drivers do not receive social security protection as workers and must pay contributions independently. Comparative studies in the United Kingdom and Singapore reveal clearer legal recognition of platform-based workers. In conclusion, regulatory reform is needed in Indonesia to align labor and social security frameworks with technological developments and ensure equal protection for online motorcycle taxi drivers.